DEVELOPING PRAGMATIC COMPETENCE IN THE EFL SETTING. THE CASE OF REQUESTS IN TOURISM TEXTS - Usó Juan, Esther; Salazar Campillo, Patricia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In this paper we present an analysis of how the speech act of requesting is offered in several EFL (English as a Foreign Language) materials from the discipline of tourism. Our objective is to examine which is the most common request structure presented in the recorded material in order to see the range of requests presented to students. The request strategies are analysed according to the taxonomy proposed by Trosborg (1995), who divided them into four main categories: indirect requests, conventionally indirect (heareroriented conditions), conventionally indirect (speaker-oriented conditions), and direct requests. In a previous study (Salazar and Usó, in press) we analysed the request strategies presented in the written materials and the exercises students had to perform in order to practise this speech act. We found that the second category, conventionally indirect requests (heareroriented conditions), is the most common category used by all textbooks under study. Results from the present study corroborate the finding that the second category is the most frequent strategy used in the tapescripts students have to listen to. There seems to be a connection between the request structures students are presented with in the written texts and the recorded materials. We propose several tasks in order to widen the scope of the requests taught to students so as to incorporate pragmatic aspects.